Application of Swedish Massage Therapy for Lower Extremities to Alleviate Muscle Cramps in Chronic Kidney Disease Patients - Ma'ruf, M. Rizky; Anggeria, Elis; Siregar, Ryskina Fatimah; Sinaga, Elvina Sari; Aminah; Rahmi, Intan Mutia; Siregar, Patimah Sari; Kaban, Fitriyana Br (Futurity Medicine, 2024)
Swedish Massage is a non-pharmacological therapy recommended to reduce muscle cramps for patients with chronic kidney disease during hemodialysis treatment. Aims: To provide a nursing care with Swedish Massage of lower extremities therapy in order to reduce muscle cramps in patients with chronic kidney disease. Methodology: This descriptive study aimed to characterise the use of Swedish massage for alleviating muscle cramps among hemodialysis patients. Results: Mr. A's pain scale score after given Swedish massage decreased from 6 to 1 and Mr. S's score decreased from 4 to 0. Scientific Novelty: It is significant for advancing theoretical understanding. Conclusion: Swedish Massage therapy has been shown to alleviate muscle cramps.